Marriage in an immigrant society: Education and the transition to first marriage in Hong Kong - Zhou, M; Wu, X; He, G (Max Planck Institute for Demographic Research, 2017)
Background: The prevalence of marriages between locals and immigrants is likely to alter the relationship between education and marriage. However, there has been little empirical research on the implications of a large immigration population for the relationship between education and marriage. Hong Kong provides an ideal setting to investigate this issue. Methods: This article examines the role of education in union formation for both men and women across two birth cohorts and the effect of education on marriages with local or immigrant spouses, using data from the 2011 Hong Kong Population Census and the Hong Kong Panel Study of Social Dynamics [HKPSSD]. Results: In contrast to findings in many other societies, local men’s education has little effect on union formation. Further analysis reveals that their education is positively associated with marrying a Hong Kong born spouse but negatively associated with marrying an immigrant spouse born in mainland China. For local women, education has a negative effect on marrying either local or immigrant spouses, but this effect diminishes over time. These findings suggest an increasing importance of women’s economic prospects in union formation in a society like Hong Kong with a high cost of living. Contribution: As the first study analysing the role of education on men and women’s marriages over time and with local or immigrant spouses in Hong Kong, this article shows the growing importance of women’s economic prospects in union formation. It also demonstrates that the presence of an enlarged pool of potential partners due to immigration can moderate the commonly assumed positive relationship between men’s education and marriage.